2015
DOI: 10.7314/apjcp.2015.16.14.5817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Breast Health Awareness Activity on the Knowledge Level of the Participants and its Association with Socio-Demographic Features

Abstract: The developing countries have higher mortality rates for breast cancer. A reason for this is presentation at advanced stages due to low levels of public awareness. Activities are arranged by health authorities of developing countries to increase the knowledge of women but their effectiveness has not been evaluated in detail. A multiple choice questionnaire with questions about socio-demographic profile and questions about breast cancer knowledge was designed in local language Urdu, to evaluate the knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…15 In contrast, a previous study (2010) that surveyed Pakistani women revealed that 46% of the women performed BSE. 16 Our study also revealed, 33.3% performed BSE on monthly basis and 17.3% performed BSE on yearly basis. In comparison, another study in Korea showed monthly performance of BSE was 13.2% although 87% women were aware of BSE.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…15 In contrast, a previous study (2010) that surveyed Pakistani women revealed that 46% of the women performed BSE. 16 Our study also revealed, 33.3% performed BSE on monthly basis and 17.3% performed BSE on yearly basis. In comparison, another study in Korea showed monthly performance of BSE was 13.2% although 87% women were aware of BSE.…”
mentioning
confidence: 68%
“…18 In addition only 14% of the female students ever received CBE and similar results stating 15% women received CBE were reported by a previous research in Pakistan. 16 However, another study in UAE showed almost half (49.4%) female respondents received CBE. 19 This huge difference between the results of studies of UAE and Pakistan can be linked to socio-cultural differences between the countries, as our report indicates (14.3%) females mentioned embarrassment as the cause of not receiving CBE.…”
mentioning
confidence: 99%
“…Of the seven studies that examined knowledge as the primary outcome, five controlled intervention studies demonstrated improvement in knowledge of health care professionals through video training, presentations, discussions, role‐plays, and learning through the review of academic papers and booklet material . Two quasi‐experimental studies that used audio‐visual educational activities demonstrated significant improvement in knowledge scores for breast cancer .…”
Section: Resultsmentioning
confidence: 99%
“…Women education about the danger of breast cancer and importance of screening should be developed for the early detection of breast cancer (Tariq, Khubaib, Imran & Ibrahim, 2011).Attentive actions are operative to increase the information of women and well influence is allied with higher education and youthfulness of women (Khokher et. al., 2015).…”
Section: Review Of Literaturementioning
confidence: 99%